Planejamento, síntese e avaliação da atividade anti-inflamatória do Nitro-Salicilato de Metila in vitro em macrófagos. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Inflammation is a series of protective and regenerative responses from the human body, characterized by a series of events involving inflammatory mediators such as cytokines and cells, being classified as acute or chronic inflammation. Throughout this process are involved leukocyte migration, recognition of PAMPs and DAMPs by TLRs receptors by tissue macrophages, production of nitric oxide, cytokines and eicosanoids such as PGE2. Nonsteroidal anti-inflammatory drugs (NSAIDs) appear among the most consumed and their action is due to the mechanism of inhibition of COX enzymes, corticosteroids are drugs that have anti-inflammatory effects with mechanism of action associated with binding with glucocorticoid receptors, cytosolic, regulating gene expression of immune cells. About salicylates, they have anti-inflammatory effects, as well their derivatives, on the other hand, have a number of adverse reactions from which we can mention the gastrointestinal, renal and cardiovascular problems. The creation of new molecules has become an art for scholars in the field, seen to the need correlated the pharmaceuticals industries, techniques like these are important for the development of new pharmaceuticals products such as those used for salicylates. NSAIDs have proven toxicity and are considered harmful to the renal and gastrointestinal and cardiovascular systems, therefore, methyl salicylate derivatives, with their anti-inflammatory effects, are an option in the development of new drugs to be used to combat inflammation. The aim of this study is to design, synthesize and evaluate the antiinflammatory activity of Methyl Nitro-Salicylate in vitro in macrophages. To obtain the NSM, we started from a reaction performed between three compounds, the assembly and production of this new drug were executed in partnership with the Pharmaceutical Chemistry Laboratory of the Federal University of Pará. Cell viability was performed by the MTT method, the production of NO was by the Griess method, the dosages of IL-1β, TNF-α and PGE-2 were quantified by the ELISA method. As result, the reaction performed between three compounds resulted in the formation of Methyl Nitro-Salicylate. NSM did not promote cytotoxic effect on concentrations below 300 μM after 24 hours of incubation, causing cell death at a concentration of 1000 μM. Regarding the tests of NO, TNF-α, IL-1β and PGE2, the results showed that NSM promoted a significant reduction in the production of these inflammatory mediators in the groups simulated with LPS + INF-γ and treated with concentrations of 12.5, 25 and 50 µM where it was possible to observe a dose dependent effect. However, NSM has been shown to have a potential anti-inflammatory effect, however, further studies should be conducted in order to identify the mechanism of action by which NSM can exert its antiinflammatory effect.
Keywords: Inflamação; Nitro-Salicilato de Metila; AINES; Mediadores Inflamatórios; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA